Hukum dan Kemerdekaan Untuk Menyatakan Pendapat - Mukantardjo, Rudy Satriyo (LAW REVIEW, 2004)
The essence of the freedoom of the press was given in one clear sentence by Lord Mansfield in a famous case "the liberty of the press consist in printing without any previous license, subject to the consequences of the law. " The classical statement on the subject is, however, to be found in Blackstone s commentaries on the laws of England In addition and as his 18th century english is still very quatable, it shall read the passage to you: "the liberty of the press is essential to the nature of a free state: but this consists is laying no